Effect of environmental factors on the abundance variations of two native rodents in agricultural systems of Buenos Aires, Argentina - Guidobono, Juan Santiago (2019)
Our aim was to assess the effect of environmental factors on short temporal abundance variations of the two most abundant native rodents of agricultural agroecosystems, Akodon azarae and Calomys laucha. We conducted a 3-year longitudinal sampling of rodents, and recorded meteorological data such as temperature and precipitation, predation rate by Leopardus geoffroyi, Tyto furcata and Athene cunicularia, vegetation cover and height, characteristics of cropfields and their borders. The effect of these factors on rodent abundance was evaluated through generalized linear mixed models. Abundance variations of both rodent species were explained by characteristics of both cropfields and their borders. At the studied temporal scale, meteorological variables did not have a direct effect on abundance variations, but probably influenced through vegetation characteristics and were expressed in seasonal variations. For A. azarae there was also an effect of predation by L. geoffroyi (positive) and T. furcata (negative), while predation by A. cunicularia did not contribute to explain abundance variations of any species.